Facile green synthesis of fingernails derived carbon quantum dots for Cu2+ sensing and photodegradation of 2, 4-dichlorophenol. Issue 1 (February 2021) - Tai, Jun Yan; Leong, Kah Hon; Saravanan, Pichiah; Tan, Sin Tee; Chong, Woon Chan; Sim, Lan Ching
Graphical abstract: Highlights: FN-CQDs were produced via hydrothermal treatment of human fingernails. Produced FN-CQDs were sensitive to detect Cu 2+ ions as low as 1 nM concentration. FN-CQD/g-C3 N4 (50) composite successfully removed 100 % of 2, 4-DCP in 75 min. FN-CQDs enable photosensitizing effect and extend lifespan of charge carriers. Abstract: The present study reports a facile method to prepare carbon quantum dots (CQDs) via hydrothermal treatment using human fingernails as a green precursor. Fingernails derived CQDs (FN-CQDs) could selectively detect copper ions (Cu 2+ ) at the concentration as low as 1 nM. Different weightage of FN-CQDs (30 wt%, 40 wt% and 50 wt%) were coupled with pure graphitic carbon nitride (g-C3 N4 ) to remove 2, 4-dicholorophenol (2, 4-DCP) under sunlight irradiation. The composite loaded with 50 wt% of FN-CQD removed 100 % of 2, 4-DCP in 75 min, which was almost 2 times higher than g-C3 N4 . The photocatalytic performance was in agreement with ultraviolet–visible diffuse reflectance spectra (UV–vis DRS) in which the photosensitizing effect was significantly exerted by 50 wt% of CQDs. In the presence of FN-CQDs, g-C3 N4 was sensitized by sunlight with an average light intensity of ∼ 937 × 100 lx to donate more electrons for the generation of oxidizing radicals. Excessive loading of FN-CQDs (up to 50 wt%) created trap state that decreased the charge carrier transport in FN-CQDs/g-C3 N4 (50). Such drawbacks did not affect the overall performance of FN-CQDs/g-C3 N4 (50). The higher loading of FN-CQDs exerted stronger photosensitizing effects to overcome the limitation of high recombination rate of charge carriers and lower surface area. FN-CQDs could act as photosensitizer to increase the light absorption range to generate more electron and holes. It also served as electron reservoir for the reduction of oxygen molecule to produce superoxide anion radical ( O2 − ). Scavenging tests identified that O2 − was the most active radical in the photodegradation of 2, 4-DCP.